Determinants of physiotherapy compliance for low back pain patients in Medan Teaching Hospital 2016 - Anita Andriany; Erna Mutiara; Halinda Sari Lubis (Fakultas Kedokteran Universitas Gadjah Mada, 2019)
Purpose: The high rate of non-compliance with physiotherapy was 71.7% in LBP patients in Medan Education Hospital in 2016. The purpose of the study was to determine the variables that are related and most related to compliance with physiotherapy.Method: The sample size of the cross-sectional study was 125 people and was chosen by simple random sampling. The type of data used is primary data through direct interviews with LBP patients who do physiotherapy at Medan Teaching Hospital using a questionnaire. Result: The results of data processing obtained the value of RP family income of 0.764 (0.337-1.732), p>0.005 not related to compliance with physiotherapy. The role of health workers is Rp. 2.453 (1.084-5.550), p<0.005 and accommodation values are Rp. 3,076 (1.159-8161), p<0.005 related to Compliance with physiotherapy. Conclusion: Accommodation is the variable most associated with compliance with physiotherapy so that the estimated number of RP is 1.897 with 95% CI (1.210-2.974) and p <0.050. LBP patients with adequate accommodation are estimated to give an opportunity 1.897 times to obey physiotherapy.